Skin disorders affecting the feet - M. H. Motswaledi (South African Family Practice)
Skin disorders of the feet can affect the glabrous skin on the dorsal aspects, or the thick skin on the plantar aspects, thereof, or both. Some can affect one foot, and others both of them. These diseases can be inflammatory, genetically inherited, infectious and neoplastic in origin. It is important to identify them and to start treatment early. If not treated, some may lead to severe pain on walking, the inability to wear shoes, and amputation with serious disability.